Bohemisms in Old Belarusian «Book of Taudal the knight» - Aleksiayevich, Hanna V. (Journal of the Belarusian State University. Philology, 2021)
The study of Czech language influence on Old Belarusian is conducted in two main directions: the study of Bohemisms in the context of Czech-Polish-Belarusian language relations in the 14th–18th centuries and the analysis of Old Belarusian written monuments, which are translations of Old Czech editions. The first direction of research takes into account the role of the Polish language as an intermediary in the process of assimilation of Bohemisms by Old Belarusian, respectively the way of penetration of Czech borrowings into the Old Belarusian language was indirect. The second direction is focused on the study of Bohemisms borrowed directly from Old Czech sources. It is known that some Old Belarusian monuments such as Biblical translations by F. Skaryna, «Tale of Sivilla the prophetess», «Song of songs» from the manuscript 588 of Synod collection, «Book of Taudal the knight», «Book of Tovit» go back to the Czech editions. The Bohemisms found in the named monuments are direct borrowings of Czech origin. This article deals with one of such Old Belarusian monuments which is «Book of Taudal the knight». Mainly attention is paid to a detailed etymological analysis of the Bohemisms preserved in the text (вражделникъ, горкость, мръха, ѡскварокъ, повлаць, прелишь, штиръ). Other Slavic loanwords, Polonisms and Church Slavic (Old Slavic) are also noted. The obtained results deepen the problems of inter-Slavic language interaction, in particular the Czech language influence on the Old Belarusian written language.